Dynamic Model of Tuna Logistics System in Padang City - Bimas Saputra, Ebit; Maharani, Amalina; Saputra, Farhan (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Indonesia is a maritime country that has large fishery resource potential and is spread over 11 Fishery Potential Areas (WPP). Therefore this research was conducted in order to obtain alternative strategies that can be implemented in an effort to increase the supply of tuna in the city of Padang using a system dynamic method approach. Based on the results obtained, increasing the amount of tuna supply can be done through existing policies in each scenario. The policies that can be carried out are: providing a fuel subsidy policy if scenario 1 is implemented, investing in the procurement of longline tuna vessels, licensing policies for increasing company capacity, and providing a fuel subsidy policy if scenario 2 is implemented, investing in the procurement of traditional vessels, investing in the procurement of longline tuna vessels, policies licensing for company capacity building, and providing fuel subsidy policies if scenario 3 is implemented. Determining the policies to be implemented for the next few years, this depends on policy makers who have considered the advantages and disadvantages of each scenario.